2022
DOI: 10.1007/s11033-021-06997-4
|View full text |Cite
|
Sign up to set email alerts
|

Role and relevance of fish cell lines in advanced in vitro research

Abstract: Introduction Cell line derived from fish has been established as a promising tool for studying many key issues of aquaculture covering fish growth, disease, reproduction, genetics, and biotechnology. In addition, fish cell lines are very useful in vitro models for toxicological, pathological, and immunological studies. The easier maintenance of fish cell lines in flexible temperature regimes and hypoxic conditions make them preferable in vitro tools over mammalian cell lines. Great excitement has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 115 publications
(122 reference statements)
0
20
0
Order By: Relevance
“…The unhindered growth of fish cell lines is caused by the high telomerase activity of adult fishes (Lund et al, 2009). Unlike mammalian cells, for fish cells, it could be shown, that these cells seem to immortalize spontaneously without any treatment (Bols et al, 2005; Goswami et al, 2022). This leads to unlimited use under perfect cultivation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The unhindered growth of fish cell lines is caused by the high telomerase activity of adult fishes (Lund et al, 2009). Unlike mammalian cells, for fish cells, it could be shown, that these cells seem to immortalize spontaneously without any treatment (Bols et al, 2005; Goswami et al, 2022). This leads to unlimited use under perfect cultivation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While Fryer and Lannan ( 84 ) listed 152 fish cell lines, Lakra et al ( 85 ) identified 283 cell lines, and these numbers keep increasing. Fish cell lines have been frequently used for the diagnosis of fish diseases as well as to study immunological responses [e.g., ( 54 , 86 , 87 )]. Table 1 lists examples of cell lines derived from fish immune tissues including cell lines for which immunological functions have been demonstrated and cell lines for which no such characterization is available.…”
Section: Fish Immune Cells In Vitro : Cell Lines A...mentioning
confidence: 99%
“…In recent years, fish cell culture has emerged as a promising in vitro model for toxicity, immunological studies, and disease diagnostics [ 16 ]. The particularities of fish cell lines, such as ease of maintenance, culture conditions, and the feasible reproducibility of the research, make this a perfect model for in vitro evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Several fish immune response studies have used fish cell lines derived from macrophages and leukocytes. Furthermore, studies have used fish cell lines to evaluate the immune response against antigens and establish a correlation with in vivo vaccine trials [ 16 ]. For instance, recombinant proteins and synthetic peptides from rhabdoviral hemorrhagic septicemia virus (VHSV) were evaluated as vaccines in suspensions of trout blood leukocytes and lymphoid organs cultures, showing an increase in leukocyte proliferation and recognition by anti-VHSV Mab.…”
Section: Introductionmentioning
confidence: 99%